2005
DOI: 10.1002/anie.200500992
|View full text |Cite
|
Sign up to set email alerts
|

Large‐Scale Nonhydrolytic Sol–Gel Synthesis of Uniform‐Sized Ceria Nanocrystals with Spherical, Wire, and Tadpole Shapes

Abstract: Spawning nanostructures: Uniform‐sized ceria nanocrystals with sphere, wire, and tadpole shapes were synthesized from the nonhydrolytic sol–gel reaction of cerium(III) nitrate and diphenyl ether in the presence of appropriate surfactants. The picture shows a TEM image of a batch of tadpole‐shaped nanowires (bottom left) and low‐magnification and high‐resolution TEM images of a single tadpole‐shaped nanowire (right and top left, respectively).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
157
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 255 publications
(162 citation statements)
references
References 75 publications
5
157
0
Order By: Relevance
“…[67] Wires with different lengths were produced by using different amounts of oleic acid, but also in this case the thickness was found to remain constant.…”
Section: Ligand Controlmentioning
confidence: 92%
“…[67] Wires with different lengths were produced by using different amounts of oleic acid, but also in this case the thickness was found to remain constant.…”
Section: Ligand Controlmentioning
confidence: 92%
“…In addition, both pure and rare earth-ion doped ceria find potential applications as oxygen ion conductors in solid oxide fuel cells, gate oxides in metal oxide semiconductor devices and ultraviolet (UV) blocking materials in UV shielding (Yu et al 2005;Miki et al 1990;Tsunekawa et al 2000). Nanostructured CeO 2 has been prepared by various methods (Sathyamurthy et al 2005;Yin et al 2002;Taniguchi et al 2008;Godinho et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Lykhach [13,14] also found that CeO 2 activation led to the rapid formation of carbonate and surface carboxylates. Meanwhile, various 1D and 2D CeO 2 nanostructures, [15][16][17] including nanorods, [18] nanowires, [19] nanotubes, [20,21] nanobelts [22,23] and other morphologies [24][25][26][27][28] had been synthesized via the thermal decomposition of CeCO 3 OH precursors, which was often prepared by solution precipitation, [29] sol-gel, [30] microemulsion, [31] sonochemical, [32] hydrothermal methods. [33] However, these synthetic processes usually were complicated with high synthesis cost due to the expensive templates and additives.…”
Section: Introductionmentioning
confidence: 99%